Use of String of Pearls Locking Plate System for Stabilization of Femoral Fractures in Canines - Reddy, G.V. Ashok Kumar; Kumar, V. Gireesh; Raghavendera, K. B. P.; Kumar, D. Pramod (International Journal of Livestock Research, 2020)
The present clinical study was conducted to evaluate String of Pearls Locking plates (SOP) in the treatment of femoral fractures in dogs. The symptoms observed in the dogs were pain on manipulation, abnormal angulation, lameness swelling, non-weight bearing, dangling of the limb and crepitation at the fracture site. Fractures were confirmed using radiography and evaluated preoperative haematological and serum biochemical parameters. Fractures were stabilized with string of pearls locking plates. String of Pearls Locking plates (SOP) was successful in the treatment of femoral fractures and offered good recompense and remarkable improvement in limb function in five out of seven dogs.